Transplanting international courts : the law and politics of the Andean Tribunal of Justice - Alter, Karen J.; Helfer, Laurence R. (Oxford : Oxford University Press, 2017)
The Andean Tribunal of Justice was established as part of the 1969 Andean Pact, as one of 11 tribunals modelled on the European Court of Justice (ECJ). This book examines the origins, practice, politics and theory of the court and compares it with the ECJ, showing why the two courts have developed differently.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 5, 2017).
Keywords: Tribunal de Justicia del Acuerdo de Cartagena; Cartagena Agreement -- (1969); Courts -- Andes Region; Andes Region -- Politics and government; Law; Laws of specific jurisdictions & specific areas of law